ASEAN+3 bond market guide 2017 Brunei Darussalam. (Metro Manila, Philippines Asian Development Bank, 2017)
Since 2006, the government has maintained a continuous program of sukuk (Islamic bond) issuance with progressively longer maturities. The objective of the current program is to both develop Brunei Darussalams yield curve as a benchmark for corporate sukuk and provide a safe and liquid investment instrument for domestic financial institutions.Brunei Darussalam has been a pioneer in issuing short-term sukuk with maturities of 1 year or less. Through June 2017, a total of 146 government sukuk using the principle of alijarah (issuance based on underlying assets) had been issued, bringing the cumulative amount issued to BND10.97 billion, with an outstanding amount of BND393.2 million as of 30 June 2017.
Keywords: Brunei -- Economic integration; Finance -- Economic aspects; Electronic books